Assessing laboratory specimen losses for the city of Johannesburg, South Africa - Naseem Cassim; Ernest P. Buthelezi; Somayya Sarang; Sadhaseevan Moodly; Lucia Hans; Lindi-Marie Coetzee (African Journal of Primary Health Care & Family Medicine)
Background: Specimen losses across the pathology value chain (PVC) result in missed diagnostic opportunities. It is difficult to fully assess these due to the current paper-based systems, with tracking of specimens only possible on the laboratory information system (LIS).